2018
DOI: 10.1177/2056305118764437
|View full text |Cite
|
Sign up to set email alerts
|

Refugees and Network Publics on Twitter: Networked Framing, Affect, and Capture

Abstract: This article constitutes a big data study of Twitter during the peak of the so-called refugee crisis in the period between October 2015 and May 2016. The article analyzed almost 7.5 million tweets collected through hashtags such as #refugee, #refugeecrisis, # flüchtling, and others. Theoretically, the article draws on concepts such as hybrid media, affective publics, networked framing, and voice. In the context of any increasingly hybrid media, we ask what are the frames on refugees that emerge on Twitter, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(110 citation statements)
references
References 31 publications
7
99
1
3
Order By: Relevance
“…After the initial counter-narrative there has been little evidence of contestation of the ongoing use of #StopIslam in relation to more recent attacks in Manchester and London. The dynamics of the #StopIslam hashtag, along with others (Evolvi, 2017;Siapera et al, 2018 and the other papers in this special edition), demonstrates the strategic and instrumental use of social media by right-wing activists, where Twitter is just one component of a more complex media ecology that is working to push mainstream political discussion to the right. In this context, it is particularly important to understand the dynamics of critical counter-narratives and the political possibilities they can (or indeed cannot) offer.…”
Section: Poole Et Al: Contesting #Stopislammentioning
confidence: 71%
See 1 more Smart Citation
“…After the initial counter-narrative there has been little evidence of contestation of the ongoing use of #StopIslam in relation to more recent attacks in Manchester and London. The dynamics of the #StopIslam hashtag, along with others (Evolvi, 2017;Siapera et al, 2018 and the other papers in this special edition), demonstrates the strategic and instrumental use of social media by right-wing activists, where Twitter is just one component of a more complex media ecology that is working to push mainstream political discussion to the right. In this context, it is particularly important to understand the dynamics of critical counter-narratives and the political possibilities they can (or indeed cannot) offer.…”
Section: Poole Et Al: Contesting #Stopislammentioning
confidence: 71%
“…3 In line with these questions of voice, the distinctive role of social media is often articulated as its relationship with the mainstream media. For instance, there is a strong tradition of work that has offered informative applications of late-Habermasian accounts of the public sphere to explore the -often complex and contradictory ways -that digital media can facilitate counter-publicity and the formation of counter-publics who can contest hegemonic media framings (Downey and Fenton,3 For a fuller discussion of 'voice' within networked digital platforms see Siapera et al, 2018 and for a specific elaboration on the concerns raised by Couldry, see Feshami (2018), this edition. 2003; de Jong, Shaw and Stammers, 2005).…”
Section: Visibility and Voicementioning
confidence: 99%
“…d Immigration policy has regrettably become the centrepiece of this transnational struggle for political power. e a Siapera et al, 2018. b Mounk and Foa, 2018.…”
Section: Transnational Tribalism Immigration and Social Media Platformsmentioning
confidence: 99%
“…The analysis used in this paper is shaped by previous studies on Twitters and its roles in the political world, particularly on the analysis of how the constructed messages on Twitter can assist the political mission of politicians in both real and digital world [9][10][11][12][13]. The previous studies indicated that building active digital followership through social media platform can serve as a crucial part of a successful political career.…”
Section: A Twitter and Politicsmentioning
confidence: 99%